Tissue Response and Immunoexpression of Interleukin 6 Promoted by Tricalcium Silicate–based Repair Materials after Subcutaneous Implantation in Rats - Andrade, Aline S. [UNESP]; Silva, Guilherme F. [UNESP]; Camilleri, Josette; Cerri, Estela S. [UNESP]; Guerreiro-Tanomaru, Juliane M. [UNESP]; Cerri, Paulo S. [UNESP]; Tanomaru-Filho, Mário [UNESP] (Elsevier, 2018)
Introduction: The aim of the present study was to evaluate the inflammatory response induced by experimental tricalcium silicate cement with 20% zirconium oxide (TSC) and MTA Plus (MTAP; Avalon Biomed Inc, Bradenton, FL) in rat subcutaneous tissues. Methods: Polyethylene tubes were filled with TSC (n = 20) and MTAP (n = 20) and implanted in the dorsal subcutaneous tissues of 32 rats. Empty tubes were used as the control (control group [CG], n = 20). After 7, 15, 30, and 60 days, the tubes with connective tissue were removed, and the inflammatory cells and immunolabeled cells for interleukin 6 (IL-6) were counted. Data were statistically analyzed using analysis of variance and the Tukey test (P ≤.05). Results: An increased number of inflammatory and immunolabeled cells for IL-6 were observed at 7 days. The number of inflammatory cells was higher for TSC and MTAP than the CG (P <.001) at 7 days; after 30 and 60 days, no significant differences were observed among the TSC, MTAP, and CG (P =.955). The number of immunolabeled cells for IL-6 was similar for TSC, MTAP, and CG at all evaluated periods. A gradual and significant decrease was observed in the number of inflammatory cells and IL-6–immunopositive cells. At 60 days, the capsules adjacent to TSC and MTAP exhibited fibroblasts and bundles of collagen fibers. Conclusions: TSC and MTAP caused a similar subcutaneous reaction in rats, suggesting that they are biocompatible and present similar immune responses.
Keywords: Biocompatibility; immunohistochemistry; interleukin 6; tricalcium Silicate; zirconium oxide